Pengaruh Ukuran Perusahaan dan Laba terhadap Audit Delay pada Perusahaan Manufaktur - Idris, Nur Irsan; Afiah, Nur (Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study aims to determine company size has a significant effect on audit delay and company profit/loss has a significant effect on audit delay. The sample of this research is a manufacturing company that experienced successive audit delays and was listed on the Indonesia Stock Exchange (IDX) in 2016-2018. This research is quantitative in nature which emphasizes its analysis on numerical data (numbers). Data collection in this study was based on documentation techniques. The results of the research and data analysis conclude that company size has a positive and significant effect on audit delay as well as profit/loss has a positive and significant effect on audit delay in manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018. This study aims to determine company size has a significant effect on audit delay and company profit/loss has a significant effect on audit delay. The sample of this research is a manufacturing company that experienced successive audit delays and was listed on the Indonesia Stock Exchange (IDX) in 2016-2018. This research is quantitative in nature which emphasizes its analysis on numerical data (numbers). Data collection in this study was based on documentation techniques. The results of the research and data analysis conclude that company size has a positive and significant effect on audit delay as well as profit/loss has a positive and significant effect on audit delay in manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018.Keywords:  audit delay, firm size, profit, manufacturing company